Adoption of routine telemedicine in Norwegian hospitals: progress over 5 years. Issue 1 (December 2016) - Zanaboni, Paolo; Wootton, Richard
Abstract Background Although Norway is well known for its early use of telemedicine to provide services for people in rural and remote areas in the Arctic, little is known about the pace of telemedicine adoption in Norway. The aim of the present study was to explore the statewide implementation of telemedicine in Norwegian hospitals over time, and analyse its adoption and level of use. Methods Data on outpatient visits and telemedicine consultations delivered by Norwegian hospitals from 2009 to 2013 were collected from the national health registry. Data were stratified by health region, hospital, year, and clinical specialty. Results All four health regions used telemedicine, i.e. there was 100 % adoption at the regional level. The use of routine telemedicine differed between health regions, and telemedicine appeared to be used mostly in the regions of lower centrality and population density, such as Northern Norway. Only Central Norway seemed to be atypical. Twenty-one out of 28 hospitals reported using telemedicine, i.e. there was 75 % adoption at the hospital level. Neurosurgery and rehabilitation were the clinical specialties where telemedicine was used most frequently. Despite the growing trend and the high adoption, the relative use of telemedicine compared to that of outpatient visits was low. Conclusions Adoption of telemedicine is Norway was high, with all the health regions and most of the hospitals reporting using telemedicine. The use of telemedicine appeared to increase over the 5-year study period. However, the proportion of telemedicine consultations relative to the number of outpatient visits was low. The use of telemedicine in Norway was low in comparison with that reported in large-scale telemedicine networks in other countries. To facilitate future comparisons, data on adoption and utilisation over time should be reported routinely by statewide or network-based telemedicine services.